Flame spreading and burning of high- and low-flash point fuels under compressed air foam suppression - Fengyuan Tian; Jun Fang; Shangqing Tao; Kun Wang; Hassan Raza Shah; Xuqing Lang; Zhijian Tian; Fei Tang (Case Studies in Thermal Engineering)
Firefighting foam has been widely used as an efficient and clean agent for extinguishing liquid fires. In this work, the flame spreading and burning of 0# diesel and n-heptane fuels were suppressed using pre discharged compressed air foam (half coverage of the pool). The foam can effectively prevent the liquid-phase-controlled flame spreading over diesel, but cannot prevent the gas-phase-controlled flame spreading of n-heptane. In the burning stage, for diesel, in the flame-foam interaction region, internal fuel flow was observed and theoretically investigated. Meanwhile, the foam layer gradually regresses as it is destroyed by the flame, with a smaller regression rate at a higher foam expansion ratio. Furthermore, the global burning rate of diesel slightly decreases compared with that of no foam discharge, but regardless of the foam expansion ratio or thickness. For n-heptane, total burning develops on the no-foam and foam areas, where the temperature increase rate of the foam-covered fuel decreases mainly depending on the initial foam mass, and the reduction of the radiation heat feedback is mainly related to the foam layer thickness. Meanwhile, foam bubbles are prone to coalescence on the n-heptane surface, which reduces the foam stability and allows it to degrade more quickly. This work helps clarify the mechanisms of foam suppression on high- and low-flash point fuel fire and serves as a guide for engineering applications.